Holistic and integrated education model (HIME) for nurturing spiritual intelligence among entrepreneur students at Batam Indonesia - Rohana, Hamzah; Mallanti, Andi; Sarimah, Ismail; Haslinda, Hashim (2016)
The existing module of entrepreneurship education available at vocational high school does not integrate spiritual intelligence into their subjects. Thus, there is a need to develop a model as a reference to develop a module with the aim and purpose to nurture spiritual intelligence among the entrepreneur students which are belief and faith of God and hold self-responsibilities as a khalifah or leader. Therefore, the researcher has developed Holistic and Integrated Entrepreneur Model and Module (HIME) to inculcate spiritual intelligence among the students. The purpose of this study is to determine the effects of the HIME in spiritual intelligence among entrepreneur students in Vocational High School (VHS), Batam, Indonesia. The research method is a quantitative study by using quasi experimental research design. 26 third year students from VHS Ibnu Sina have been assigned as a control group and 26 students from VHS Al-Azhar have been assigned as an experimental group. A multiple choice questionnaire has been developed; validated and pilot testing for reliability, alpha Cronbach value for the instrument is 0.89. Therefore, the instrument is reliable to use in this study. The overall finding showed that score for respondents from experimental group (86) has achieved higher score in spiritual intelligence as compared to control group (77). Therefore, the respondents’ spiritual intelligence in general increased after they infuse the HIME module.